Pengaruh Nilai Tukar, Pertumbuhan Ekonomi, Inflasi, dan Suku Bunga terhadap Investasi Asing Langsung di Indonesia - Nadya Khodijah Putri; Komara Komara; Tupi Setyowati (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
This study aims to determine the effect of the rupiah exchange rate, economic growth, inflation rates and interest rates on foreign direct investment. this study use quantitative methods. The samples in this study are the value of  the foreign direct investment net inflow, the official exchange rate, the gross domestic product per capita, the consumer price index and the lending interest rate in Indonesia in the period 1994-2019. The data used in this study are secondary data obtained from the World Bank website. Data processing and analysis techniques used are the descriptive statistics analysis, the multiple linear regression, the classic assumption tests, the correlation coefficient analysis, and the hypothesis testing. The results showed that the rupiah exchange rate partially had a negative and significant effect on the foreign direct investment, the economic growth had a positive and significant effect on the foreign direct investment, the inflation rate had a positive and significant effect on the foreign direct investment and the interest rate had a negative influence and significant impact on the foreign direct investment against foreign direct investment. Simultaneously, the Rupiah exchange rate, economic growth, inflation,  and interest rates have a significant influence on the  foreign direct investment in Indonesia